The relationship between hyperuricemia and atrial fibrillation in patients with heart failure (Annals of Medical Research, 2023)
Aim: Uric acid is the end product of purine metabolism. Overproduction and insufficient excretion cause an increase in serum uric acid (SUA) levels. In some studies, it has been shown that hyperuricemia is an independent predictor of cardiovascular mortality and poor prognosis of heart failure (HF). It has been found that the level of SUA may also be a biomarker to be used in demonstrating inflammation and oxidative stress. Recent studies have shown that inflammation and oxidative stress play a role in the pathogenesis of both HF and atrial fibrillation (AF). In this study, we aimed to investigate whether the level of SUA is associated with the development of AF in patients with HF.Materials and Methods: A total of 1,342 patients with HF who applied to outpatient clinic between 2018 and 2022 were scanned. Patients with one of the exclusion criteria were not included in the study. As a result, 538 HF patients were included. These patients were divided into 2 groups as new-diagnosed AF patients and patients without AF.Results: SUA level was 9.29±2.93 mg/dL in patients with AF and 7.67±2.5 mg/dL in patients who did not develop AF, which was statistically significant (p
Keywords: Atrial fibrillation; Heart failure; Uric acid